Stop the cassava rot - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A cassava parasite (Lasiodiplodia theobromae), found in the 1990s in the mountainous region of Togo the Danyi Plateau and the Adélé region causes far more damage in this region than other regions. Researchers discovered that this is due...